Streptococcus agalactiae Native Valve Endocarditis: Uncommon Presentation of Multiple Myeloma - Pinho Oliveira, Ana (2016)
Adults with chronic immunosuppressive conditions are at an increased risk for Streptococcus agalactiae endocarditis, which is typically characterized by acute onset, presence of large vegetations, rapid valvular destruction and frequent complications. We report a rare case of a 74 years old man presenting with fever, renal infarction, ischemic stroke and uveitis. Infective endocarditis was diagnosed and Streptococcus agalactiae was isolated in blood cultures. A multiple myeloma Ig G-K was also diagnosed. The infective endocarditis was successfully treated with a course of benzylpenicillin and gentamicin. The authors highlight the severity of vascular embolic disease present in this case and the diagnostic challenge. They also intend to remind about the association between Streptococcus agalactiae endocarditis and chronic diseases, despite its low reported prevalence.